2020
DOI: 10.1080/0284186x.2020.1787506
|View full text |Cite
|
Sign up to set email alerts
|

Association between variations in the number of hospital beds and inpatient chemo/radiotherapy for breast cancer: a study using a large claim database

Abstract: Objective: Chemo/radiotherapy for breast cancer patients does not require hospitalisation in most cases. We investigated the relationship between the proportion of hospitalisation for chemo/radiotherapy over total hospitalisation and the number of hospital beds per capita among breast cancer cases. Design: A retrospective observational study. Setting: Hospitals in Japan. Participants: In total, 561,165 records of hospitalisation of breast cancer cases were extracted from the Japanese Diagnosis Procedure Combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Database-based studies are also increasing in the investigation of risk factors for disease [25,26,27,28]. Studies using databases to study breast cancer include studies on treatment selection for breast cancer and epidemiological studies of male breast cancer [29,30], but no studies have used databases to identify risk factors for BCRL. If database-based studies are shown to be useful in identifying risk factors for BCRL, it is expected that BCRL prevention activities will be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Database-based studies are also increasing in the investigation of risk factors for disease [25,26,27,28]. Studies using databases to study breast cancer include studies on treatment selection for breast cancer and epidemiological studies of male breast cancer [29,30], but no studies have used databases to identify risk factors for BCRL. If database-based studies are shown to be useful in identifying risk factors for BCRL, it is expected that BCRL prevention activities will be improved.…”
Section: Introductionmentioning
confidence: 99%